Fine sand facilitates egg extrusion and improves reproductive output in female mud crab genus Scylla - Fazhan, Hanafiah; Waiho, Khor; Shu-Chien, Alexander Chong; Wang, Youji; Ikhwanuddin, Mhd; Abualreesh, Muyassar H.; Kasan, Nor Azman; Wu, Qingyang; Muda, Sabri; Sor, Chin Siang; Jalilah, Mohamad (PeerJ, 2022)
Mud crabs (genus Scylla) are gaining attention as potential aquaculture species due to their lucrative market price and high demand. One of the essential components of mud crab culture is broodstock quality. The optimisation of mud crab broodstock culture currently focused on its nutritional aspects and common rearing parameters, including stocking density and temperature. The use of sandy substrate to induce egg extrusion in female Scylla broodstock is common; however, its optimisation has never been conducted. This study investigated (1) the substrate association of two Scylla species (S. olivacea, S. paramamosain) during broodstock conditioning until egg extrusion when the choices of fine (66.99 ± 14.48 μm) and coarse (656.17 ± 38.13 μm) sands were given; (2) the female reproductive output when S. olivacea females were individually exposed to either fine sand, coarse sand, or no sand treatments. Females, spawners and non-spawners, of S. olivacea and S. paramamosain were associated with fine sand and none was observed to bury in the coarse sand tray. The occurrence of egg extrusion was not significantly different between species but moderately associated with the duration of visits (stayed in sand for 1 d, 2 d, ≥3 d). The final incubation period in the sand tray was more than 2 days in all cases, except for one female S. paramamosain (buried in the sand for 1 day prior to egg extrusion). When no choice was available, the highest percentage (58.3%) of females extruded eggs in fine sand treatment, followed by coarse sand treatment (33.3%), and no sand treatment (8.3%). Sand type influenced the weight of egg clutch, total egg number, fecundity, and clutch size. These results suggest that fine sand (<70 μm) substrate should be incorporated into Scylla broodstock rearing to maximise female reproductive output.
Keywords: Broodstock culture; Sand size preference; Scylla; Crab farming; Egg extrusion